Longitudinal, Quantitative, Multimodal MRI Evaluation of Patients With Intracerebral Hemorrhage Over the First Year - Haque, Muhammad E.; Boren, Seth B.; Arevalo, Octavio D.; Gupta, Reshmi; George, Sarah; Parekh, Maria A.; Zhao, Xiurong; Aronowski, Jaraslow; Savitz, Sean I. (Frontiers in Neurology, 2021)
In most patients with intracerebral hemorrhage (ICH), the hematoma and perihematomal area decrease over the subsequent months but patients continue to exhibit neurological impairments. In this serial imaging study, we characterized microstructural and neurophysiological changes in the ICH-affected brain tissues and collected the National Institute of Health Stroke Scale (NIHSS) and modified Rankin Score (mRS), two clinical stroke scale scores. Twelve ICH patients were serially imaged on a 3T MRI at 1, 3, and 12 months (M) after injury. The hematoma and perihematomal volume masks were created and segmented using FLAIR imaging at 1 month which were applied to compute the susceptibilities (χ), fractional anisotropy (FA), mean diffusivity (MD), and cerebral blood flow (CBF) in the same tissues over time and in the matching contralesional tissues. At 3 M, there was a significant (p < 0.001) reduction in hematoma and perihematomal volumes. At 1 M, the χ, FA, and CBF were decreased in the perihematomal tissues as compared to the contralateral side, whereas MD increased. In the hematomal tissues, the χ increased whereas FA, MD, and CBF decreased as compared to the contralesional area at 1 M. Temporally, CBF in the hematoma and perihematomal tissues remained significantly (p < 0.05) lower compared with the contralesional areas whereas MD in the hematoma and χ in the perihematomal area increased. The NIHSS and mRS significantly correlated with hematoma and perihematomal volume but not with microstructural integrity. Our serial imaging studies provide new information on the long-term changes within the brain after ICH and our findings may have clinical significance that warrants future studies.